QUALITY CONTROL OF RAW MATERIALS FOR CANDIED CARICA USING P-CHART ANALYSIS AND FISHBONE DIAGRAM - Panjaitan, Miftah Aini; Suryantini, Any; Jamhari, Jamhari (Jurnal Aplikasi Manajemen, 2019)
Carica is a plant that can only grow in the Dieng area of Wonosobo. This causes raw materials only to be obtained in the Wonosobo area. The number of Carica processing efforts, causing entrepreneurs must be able to optimize the quality of raw materials. One of the companies that process Carica is a CV. Yuasa Food Berkah Makmur, to find out companies in asking for quality raw materials. The purpose of this study is quality control to minimize defective products produced by the company. Without the process of controlling product quality, the company will correct losses. This study was conducted to determine the quality of raw materials used in the process of making Carica candied fruit based on SQC analysis. The sample is the result of a 100% examination. The method of data analysis uses p (p-chart) control maps and causal diagrams. The results of the analysis of data testing in January to June 2018, there are two months raw material for Carica candied fruit, which is outside the boundaries of the March and April statistical data. In March there is one result of the quality of raw materials above. In April, there is one result of the quality of raw materials above the access limit. Analysis of analysis using Fishbone Diagrams found the priority due to uncontrolled quality of raw materials, human factors, raw material factors, and environmental factors.